Hook, line and sinker - Wheeler, Bert 1895-1968; Woolsey, Robert 1889-1938; Lee, Dorothy 1911-1999; Cline, Edward 1892-1961; Whelan, Tim 1893-1957; Spence, Ralph 1889-1949; LeBaron, William 1883-1958 (Digiview Productions, 2004)
Two bumbling insurance salesmen agree to help run a hotel. They are surprised to learn of the hotel's poor shape and decide they must take drastic measures to drum up business. Soon a scheme is concocted to pitch the hotel as a destination resort for the well off